Madrasah Teachers’ Approaches to Classroom Assessment - Isnawati, Ida (DIMAR: Jurnal Pendidikan Islam, 2024)
Since assessment holds a crucial role in the teaching and learning process, it is essential to examine teachers' approaches to assessment in their classrooms to determine whether their methods align with assessment theories and best practices. This study aimed to explore how madrasah teachers approach student assessment in their classrooms, focusing on the purpose of assessment, the assessment process, fairness in assessment, and the principles of measurement theory. The study involved 27 secondary-level madrasah teachers in an Indonesian context to illustrate their assessment knowledge and address the research gap in assessment studies for madrasah teachers. Their classroom assessment approaches were gathered and evaluated using the Approaches to Classroom Assessment Instrument (ACAI). The results indicate that madrasah teachers generally view assessment for learning as the primary purpose of their assessments, focus on the design aspect during the assessment process, adhere to standard principles of assessment fairness, and give equal importance to both validity and reliability in measurement theory. Finally, findings of this study should give valuable contribution to the body of assessment theory and become a reference for the government in improving madrasah teachers’ assessment literacy as well as their skills in assessing students’ learning.